Quantitative Analysis of the Multicomponent and Spectrum–Effect Correlation of the Antispasmodic Activity of Shaoyao-Gancao Decoction - Yanli Xu; Chenxi Li; Ting Chen; Xiaochun Li; Xiaoyu Wu; Qili Zhang; Lei Zhao (Journal of Analytical Methods in Chemistry)
Shaoyao-Gancao Decoction (SGD) is a well-known classic traditional Chinese medicine (TCM) with antispasmodic, anti-inflammatory, and analgesic effects. This preparation has been widely used to treat spasticity diseases in the clinic. To date, the material basis of SGD remains unclear, and the spectrum-effect correlation of its antispasmodic activity has not been reported yet. In this study, high-performance liquid chromatography (HPLC) was used to establish the fingerprint and determine the multiple components of SGD. The common peaks of fingerprints were evaluated by the similarity with the chromatographic fingerprints of the TCM. Meanwhile, the multiple components were quantified and analysed using the heatmap and box size analysis. Furthermore, data on the antispasmodic effect were extracted through in vitro smooth muscle contraction assay. Grey relational analysis combined with partial least square regression was used to study the spectrum–effect correlation of SGD. Finally, the potential antispasmolytic components were validated using an isolated tissue experiment. The HPLC fingerprint was established, and 20 common peaks were identified. The similarities of 15 batches of SGD were all above 0.965. The HPLC method for simultaneous determination of the multiple components was accurate and reliable. The contents of albiflorin, paeoniflorin, liquiritin, and glycyrrhizic acid were higher than the other components in SGD. The heatmap and box size also showed that X3 (albiflorin), X4 (paeoniflorin), X5 (liquiritin), X11 (liquirtigenin), and X16 (glycyrrhizic acid) could be used as quality indicators in the further establishment of quality standards. The spectrum–effect correlation results indicated that X4, X11, and X16 were highly correlated with antispasmolytic activity. Verification tests showed that paeoniflorin (11.7–29.25 μg/mL) and liquirtigenin (17.19–28.65 μg/mL) could significantly reduce the maximum contractile (P<0.01). These compounds exerted concentration-dependent spasmolytic effects with the inhibitory response for acetylcholine (Ach)-evoked contraction. Thus, SGD had a significant antispasmodic effect, which resulted from the synergistic activity of its multiple components. These findings can be used for the pharmacodynamics study of SGD and are of great significance for the determination of quality markers and quality control.